PENGARUH PELATIHAN KERJA, KOMPETENSI, DAN BEBAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA CV. SERAYA BUDAYA GIANYAR, BALI - Ni Nym Adhi Sukmanitri; Ni Made Dwi Puspitawati; Gde Bayu Surya Parwita (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2024)
Decreasing employee work productivity at CV. Seraya Gianyar Culture, which is caused by job training, competency, and workload, has an impact on decreasing company sales in 2022. This research was conducted with the aim of finding out and analyzing the influence of job training, competency, and workload on employee work productivity at CV. Gianyar Culture and Culture. The population in this study were all employees at CV. Gianyar Culture and Culture. The sampling method used was saturated sampling, and a sample size of 32 respondents was obtained. The data analysis technique used in this research is multiple linear regression analysis, which was tested using SPSS Version 25. The results of this research show that job training, competency, and workload have a positive and significant effect on the work productivity of CV employees. Gianyar Culture and Culture It is hoped that future researchers will be able to add other factors that influence employee productivity, such as work environment, compensation, and work discipline.